Sleep Deprivation Disturbs Immune Surveillance and Promotes the Progression of Hepatocellular Carcinoma - Huang, Jing; Song, Peiwen; Hang, Kaibin; Chen, Zeka; Zhu, Zidan; Zhang, Yuye; Xu, Jietian; Qin, Jie; Wang, Binghua; Qu, Weimin; Huang, Zhili; Liang, Chunmin (Frontiers in Immunology, 2021)
Sleep disturbance is common in patients with cancer and is associated with poor prognosis. However, the effects of sleep deprivation (SD) on immune surveillance during the development of hepatocellular carcinoma (HC) and the underlying mechanisms are not known. This was investigated in the present study using mouse models of SD and tumorigenesis. We determined that acute and chronic sleep deprivation (CSD) altered the relative proportions of various immune cell types in blood and peripheral organs. CSD increased tumor volume and weight, an effect that was enhanced with increasing CSD time. Expression of the cell proliferation marker Ki-67 was elevated in tumor tissues and tumor cell infiltration into adjacent muscles was enhanced by CSD. Multicolor flow cytometry analysis revealed that CSD significantly reduced the numbers of antitumor CD3+ T cells and NK cells and increased that of immunosuppressive CD11b+ cells infiltrating into the tumor microenvironment from the spleen via the peripheral blood. These results indicate that CSD impairs immune surveillance mechanisms and promotes immunosuppression in the tumor microenvironment to accelerate tumor growth, underscoring the importance of alleviating sleep disturbance in HC patients in order to prevent HC progression.